2010
DOI: 10.1371/journal.pone.0010658
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Triage System for Adult Patients Using an Influenza-Like Illness Scoring System during the 2009 Pandemic—Mexico

Abstract: BackgroundPandemic influenza A (H1N1) virus emerged during 2009. To help clinicians triage adults with acute respiratory illness, a scoring system for influenza-like illness (ILI) was implemented at Hospital Civil de Guadalajara, Mexico.MethodsA medical history, laboratory and radiology results were collected on emergency room (ER) patients with acute respiratory illness to calculate an ILI-score. Patients were evaluated for admission by their ILI-score and clinicians' assessment of risk for developing complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…It has been shown that the ER patient flow during influenza outbreaks significantly increases, and challenges the routine of these first-line clinical units [7]. The development of specific triage algorithms might improve their performance, as well as the infection control practices [8]. Not surprisingly, the most difficult issues to resolve within Spanish hospitals were the vaccination of healthcare professionals (HCPs) and the low awareness of HCPs regarding infection control and the prevention of influenza transmission [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the ER patient flow during influenza outbreaks significantly increases, and challenges the routine of these first-line clinical units [7]. The development of specific triage algorithms might improve their performance, as well as the infection control practices [8]. Not surprisingly, the most difficult issues to resolve within Spanish hospitals were the vaccination of healthcare professionals (HCPs) and the low awareness of HCPs regarding infection control and the prevention of influenza transmission [9].…”
Section: Discussionmentioning
confidence: 99%
“…No children aged <5 years received early treatment, and only 20% received oseltamivir within 48 hours of the physician visit. Although a previous case-series of 251 children infected with influenza A H1N1pdm with 13 fatalities did not find a difference between prompt consultation, ICU admission, survival, and oseltamivir treatment [3], we recommend early treatment based on the findings of larger case-series [31]. The apparent reluctance to provide early antivirals to young children may have been caused by the clinician's lack of familiarity with the use of oseltamivir and their concerns over potential adverse events among very young children.…”
Section: Discussionmentioning
confidence: 75%
“…We developed a scoring system using eight factors in an attempt to improve on the accuracy of the case definitions. While others have devised a simple score incorporating clinical and laboratory data in determining the likelihood of H1N1/09 pneumonia compared to other causes of community‐acquired pneumonia, or the need for hospitalization, to the best of our knowledge, this is the first scoring system based entirely on variables immediately available to the clinician 21,22 . The scoring system marginally outperformed the case definitions – score group 3, for example, had equivalent or superior predictive values to any of the CDNA definitions – and was of similar discrimination to the logistic regression (AUROC 0·73 versus 0·75).…”
Section: Discussionmentioning
confidence: 99%